The mediating influence of nation brand image in the relationship between tourism and hospitality attributes and behavioural intention - Handayani, Bintang; Rashid, Basri (Tourism Educators Association of Malaysia (TEAM), 2016)
Although past studies indicate the relationships of experience-based industry with nation brand image (NBI), only a few studies have been carried out in the context of emerging nations. In addition, among other sub-domains of place branding, NBI is considered as the least explored. This article reports on research carried out in Indonesia which examines the mediated effect of Indonesia's NBI on tourists' behavioural intention.Data collected from a survey of overseas tourists to Indonesia was analysed by Baron and Kenny's four-step mediation test. Further, the Sobel test was used to determine the significance of the z value.The findings demonstrate partial mediation of NBI on the relationship between tourism and hospitality components and behavioural intention.Overall, the findings can be used for planning and developing brand image for a nation.This study is also consistent with past studies that allude superior positioning of experiential consumption, and the strong positioning of NBI perspectives in place branding domain.